Estimation of wave parameters based on nearshore wind-wave correlations - Guner, H. Anil Ari; Yuksel, Yalcin; Cevik, Esin Ozkan (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
A statistical wave model for a specific region was developed to generate long-term wave data in case of the absence of any measured data or to fill the data gaps which occur in a measurement data. Wind data, wave measurement data and a third generation numerical wave model (MIKE21 SW) were used to develop a wave model that is applicable for the research area. The aim of to use such a model is to gain a practical and quick estimation of the wave parameters by using a meteorological station's wind parameters without having need far a sophisticated wave model which demands more complicated input parameters. In addition, previously developed wave prediction models which are less complicated should not be appropriate for every coastal zone for various reasons. Therefore, the best way to estimate the wave climate for a region is to obtain a site-specific wave model. The Karaburun coastal zone located at the southwest coast of the Black Sea was chosen as the study field. Wind, wave and water level measurements were performed to determine the field data. Wave measurements were carried out at the site by an ultrasonic and pressure type wave gauge between the dates of August 2003 and March 2005. Wave measurement data was used both for the development and calibration of the statistical wave model. The results obtained from the statistical wave model have an RMSE value of 0.29 m for the significant wave heights which is very reasonable when the model is considered to be simple and demanding less input data (wind speed, wind direction and fetch length). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Wave forecasting; Statistical wave model; Wave measurement; MIKE21 SW; Wind wave; Engineering; Oceanography